BRAND IMAGE AND BRAND ASSOCIATION AS PREDICTORS OF PURCHASE INTENTION: EXAMINING THE PRO-ISRAEL PRODUCT CONTEXT - Kurniawan Prasetyo; Siti Muslichatul Mahmudah; Muthia Rahayu (Jurnal Visi Komunikasi, 2026)
Brand image and brand association are key elements in building brand identity and perception in the eyes of consumers. Understanding how brand image and brand associations influence consumer purchase intention is critical to business sustainability. When products are associated with sensitive issues such as political issues, such as pro-Israel, it can affect consumer perception in a more complex way. The boycott, divestment, sanctions (BDS) movement calls on followers to abandon major brands because of their direct involvement in supporting Israeli atrocities against Palestinians. Pro-Israel associated products can also have associations with certain political values, beliefs or identities associated with supporting Israel. These associations can influence how consumers perceive the product. Product association with pro-Israel issues can affect consumer purchase intention. This study aims to identify and analyze the influence of brand image and brand association on consumer purchase intention on products with pro-Israel associations. The results of this study identify that brand image and brand association have a significant influence on consumer purchase intention for products with pro-Israel associations, at a rate of 68.9%. Brand image demonstrates a very strong influence (60.5%), where consumers' perceptions of the brand image affect their purchasing decisions. Similarly, a strong and positive brand association also increases purchase intention by 60.2%. The combination of a positive brand image and strong brand association simultaneously shows a highly significant impact on consumer purchase intention.